Synthesis and Biological Evaluation of New 4β-5-Fu-substituted 4(')-Demethylepipodophyllotoxin Derivatives - Zhang, Fu-Min (Molecules, 2006)
A series of new 4β-5-Fu-substituted 4(')-demethylepipodophyllotoxin derivatives were synthesized and evaluated, together with some previously prepared ones, for their cytotoxic activities against four tumor cell lines (HL60, P388, A549 and BEL7402). Three of these compounds exhibited superior in vitro anticancer activity against P388 and A549 than the reference compound etoposide. In addition, the partition coefficients (P) of all the new and previously synthesized derivatives were determined.